The Effect Of Electromagnetic Field On Hard Water Treatment And Scale Formation Using Variable Flow Rate (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Scale deposition in water pipe due to hard water circulation often leads to various technical and economical problems. The conventional chemical treatment methods uses hazardous chemical which affects human health as well as water chemistry. This study shows the effect of physical water treatment method like pulsating electromagnetic field on water characteristics and scale reduction under different turbulent flow conditions and pipe materials. The scale removal rate was analyzed by the formation of aragonite crystal in water pipes in place of calcite crystals after electromagnetic treatment. The morphology of aragonite and calcite crystals was analyzed by field emission scanning electron microscope on different pipe materials. The water flow rate was maintained at 3, 5 and 7 L/min. After electromagnetic treatment result shows that the scale removal rate increases from pipe wall and reduces the total dissolved solids (TDS), electrical conductivity (EC), hardness and alkalinity of water. These water characteristics are further decreases on increasing the flow rate from 3 to 7 L/min. The reduction rate of these water characteristics was higher for the first 15 hours of circulation time than the remaining 15 hours. On investigating the effect of electromagnetic treatment on pipe material, it was obtained that the polyvinyl chloride (PVC) pipe is much effective than galvanized iron (GI) and copper pipes.